1990
DOI: 10.1159/000261275
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chlorhexidine Gel Treatment Supplemented with Chlorhexidine Varnish and Resin on Mutans Streptococci and Actinomyces on Root Surfaces

Abstract: The supplementary effect of chlorhexidine varnish and resin on the reappearance of mutans streptococci and Actinomyces spp. on root surfaces after chlorhexidine gel treatment was studied. In 8 subjects with many restored tooth and exposed root surfaces, highly colonized with mutans streptococci, chlorhexidine varnish and resin were applied to the teeth on one side of the mouth and resin alone to the other side. This treat ment significantly prolonged the time period of reduced salivary levels of mutans strepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0
3

Year Published

1994
1994
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 18 publications
1
17
0
3
Order By: Relevance
“…The enhanced inhibitory effect is most likely due to the prolongedcontact of the antimicrobial with the dentition. The best effects have been obtained when an extra layer of polyurethane sealant (Sandham et al, 1988 or bonding resin (Fure and Emilson, 1990) has been applied over the chlorhexidine varnish, which increased the retention of chlorhexidine on the teeth for up to approximately five days . Without an extra layer, the long-term effect seems to be highly dependent on the concentration of Based ondata from: Emilson, 1981;Emilson and Fornell, 1976;Emilson etal.,1976;FureandEmilson,199a,Gisselssonetal.,1988Johansen et al, 1975Katz, 1982;Keltjens et al, 1990;Kristoffersson and Bratthall, 1982;Lindquist et al, 1989, Luoma et al, 1978Maltz et al, 1981;Mikkelsen et al, 1981;Ostela et al, 199Q0 Persson et al, 1991;Petersson et al, 1991;Sandham et al, 1988Sandham et al, ,1991Schaeken and De Haan, 1989, Schaeken et al, 1986, 1991aSpets-Happonen et al, 1985von der Fehr et al, 1975;Zickert et al, 1982;Zyskind et al, 1990. chlorhexidine in the varnish.…”
Section: Effects Of Different Modes Of Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The enhanced inhibitory effect is most likely due to the prolongedcontact of the antimicrobial with the dentition. The best effects have been obtained when an extra layer of polyurethane sealant (Sandham et al, 1988 or bonding resin (Fure and Emilson, 1990) has been applied over the chlorhexidine varnish, which increased the retention of chlorhexidine on the teeth for up to approximately five days . Without an extra layer, the long-term effect seems to be highly dependent on the concentration of Based ondata from: Emilson, 1981;Emilson and Fornell, 1976;Emilson etal.,1976;FureandEmilson,199a,Gisselssonetal.,1988Johansen et al, 1975Katz, 1982;Keltjens et al, 1990;Kristoffersson and Bratthall, 1982;Lindquist et al, 1989, Luoma et al, 1978Maltz et al, 1981;Mikkelsen et al, 1981;Ostela et al, 199Q0 Persson et al, 1991;Petersson et al, 1991;Sandham et al, 1988Sandham et al, ,1991Schaeken and De Haan, 1989, Schaeken et al, 1986, 1991aSpets-Happonen et al, 1985von der Fehr et al, 1975;Zickert et al, 1982;Zyskind et al, 1990. chlorhexidine in the varnish.…”
Section: Effects Of Different Modes Of Treatmentmentioning
confidence: 99%
“…Covering all tooth surfaces during every varnish application was more effective than partial covering of selected tooth surfaces , and recently it was shown that this full-coverage method was effective in suppressing mutans streptococci levels for long periods, even in children with fixed orthodontic -appliances (Sandham et al, 686 Emilson 1992). It has also been shown that the period of undetected and reduced salivary levels of mutans streptococci was significantly prolonged when the varnish treatment was preceded by a gel treatment in subjects with high caries experience and with exposed root surfaces (Fure and Emilson, 1990).…”
Section: Effects Of Different Modes Of Treatmentmentioning
confidence: 99%
“…[6–8] Chlorhexidine has been recommended by various authors an effective agent to disinfect dentin. [1112] It is also effective in reducing the levels of S. mutans found on exposed carious root surfaces. [11] It has been recently shown that Chlorhexidine preserves dentin bond strength by inhibiting host derived matrix metalloproteinases (MMPs).…”
Section: Introductionmentioning
confidence: 99%
“…[1112] It is also effective in reducing the levels of S. mutans found on exposed carious root surfaces. [11] It has been recently shown that Chlorhexidine preserves dentin bond strength by inhibiting host derived matrix metalloproteinases (MMPs). [13] However, any positive benefits would be negated if the solution affects the composite resin bond to dentin.…”
Section: Introductionmentioning
confidence: 99%
“…In several studies, the application of a CHX varnish on the teeth or root surfaces of patients was successful in removing oral MS or reducing the caries increment. This decrease was most prominent in studies where patients attended the dental profession regularly [Fure and Emilson, 1990;Keltjens et al, 1992;Ie and Schaeken, 1993;Bratthall et al, 1995;Petersson et al, 1998;Achong et al, 1999;Twetman and Petersson, 1999]. Some investigators showed a suppression of MS 6 months after a CHX varnish application [Schaeken et al, 1991;Sandham et al, 1992;Fennis et al, 1998].…”
mentioning
confidence: 99%